Research on the multidimensional brain remodeling mechanisms at the level of brain regions, circuits, and networks in patients with chronic lower back pain caused by lumbar disk herniation - Mei, Yuan-Dong; Gao, Hang; Chen, Wei-Fei; Zhu, Wei; Gu, Chen; Zhang, Jun-Peng; Tao, Ji-Ming; Hua, Xu-Yun (Frontiers in Neuroscience, 2024)
Introduction Chronic lower back pain (cLBP), frequently attributed to lumbar disk herniation (LDH), imposes substantial limitations on daily activities. Despite its prevalence, the neural mechanisms underlying lower back pain remain incompletely elucidated. Functional magnetic resonance imaging (fMRI) emerges as a non-invasive modality extensively employed for investigating neuroplastic changes in neuroscience. In this study, task-based and resting-state fMRI methodologies are employed to probe the central mechanisms of lower back pain. Methods The study included 71 chronic lower back pain patients (cLBP group) due to LDH and 80 age, gender, and education-matched healthy volunteers (HC group). The subjects are mainly middle-aged and elderly individuals. Visual Analog Scale (VAS), Oswestry Disability Index (ODI), and Japanese Orthopedic Association Scores (JOA) were recorded. Resting-state and task-based fMRI data were collected. Results/discussion No significant differences were observed in age, gender, and education level between the two groups. In the cLBP group during task execution, there was diffuse and reduced activation observed in the primary motor cortex and supplementary motor area. Additionally, during resting states, notable changes were detected in brain regions, particularly in the frontal lobe, primary sensory area, primary motor cortex, precuneus, and caudate nucleus, accompanied by alterations in Amplitude of Low Frequency Fluctuation, Regional Homogeneity, Degree Centrality, and functional connectivity. These findings suggest that chronic lower back pain may entail reduced excitability in sensory-motor areas during tasks and heightened activity in the sensory-motor network during resting states, along with modified functional connectivity in various brain regions.